Theologising democracy in the context of Muhammadiyah’s ijtihād - Hasnan Bachtiar; Zakiyuddin Baidhawy (IAIN Salatiga, 2022)
This article focuses to examine the process of Muhammadiyah’s ijtihād has evolved, specifically in constructing the notion of Negara Pancasila sebagai Dār al-‘Ahd wa al-Shahādah (the state of consensus and witness) and the arguments on which it is built. The scholarly issues that have been highlighted in this article are study on this specific discourse has not been done yet, the ijtihad in the field of Siyar (law of war and international relations in Islamic traditions) which has been elaborated with ideas of contemporary social sciences is very rare, and the discourse of Siyar has dominantly covered only the area of Middle East. Accordingly, this article confidently fulfils these gaps applying qualitative research method and analysis of social contextualisation. This article argues that the way of Muhammadiyah’s ijtihād in producing the idea of Indonesia as the state of consensus and witness is applying theologising democracy. It consists of trajectory in which Muhammadiyah has objectified Islam and substantialised it to enhance the meaning of democracy.